2004
DOI: 10.1021/jp040135h
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Property Correlations in Model Compounds of Oligomer Liquid Crystals

Abstract: Structure−property correlations of the following model compounds for oligomer liquid crystals (LCs) have been investigated:  monomers, C6H5O(CH2) x CH3 (x = 4 and 5); dimers, C6H5O(CH2) x OC6H5 (x = 3, 4, 5, and 6); and tetramers, C6H5O(CH2) x OC6H4O(CH2) x OC6H4O(CH2) x OC6H5 (x = 5 and 6). Deuterium NMR quadrupolar splittings observed from the deuterated model compounds dissolved in a nematic solvent, 4‘-methoxybenzylidene-4-n-butylaniline (MBBA) or p-azoxyanisole (PAA), were analyzed by the rotational isome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…The thioesters weakly show the odd-even oscillation in T m , whereas the dithioesters do show strongly. In our previous study, 29 the similar odd-even effect was clearly observed in crystal and mesophase stabilities of the model compounds of liquid crystalline polyethers.…”
Section: Odd-even Effects Of the Model Compoundssupporting
confidence: 76%
“…The thioesters weakly show the odd-even oscillation in T m , whereas the dithioesters do show strongly. In our previous study, 29 the similar odd-even effect was clearly observed in crystal and mesophase stabilities of the model compounds of liquid crystalline polyethers.…”
Section: Odd-even Effects Of the Model Compoundssupporting
confidence: 76%
“…The aliphatic linker between the aromatic rings is not in a fully stretched conformation, but has adopted an (anti, Àgauche,Àgauche,anti) conformation. This is directly comparable to the published (Sasanuma et al, 2004) nonderivatized ligand, viz. 1,3-diphenoxypropane, (II), which adopts a nearly identical conformation (Fig.…”
Section: Commentsupporting
confidence: 86%
“…As found for PEO and PPO, the polyethers often form the (C-H)‚‚‚O attractions, whose strengths depend on the number of carbon atoms between ether linkages. 74,75 In some polyethers, the former factor appears predominantly, and the latter is often superior in other polyethers. These tendencies, being sensitive to the environment, are changeable.…”
Section: Discussionmentioning
confidence: 99%